Impact of a comprehensive academic support and mentoring program on underperforming medical students: evidence from a 14-year institutional retrospective study - Herruzo, Irene; Castañeda-Vozmediano, Raúl (Frontiers in Education, 2025)
IntroductionAcademic underperformance among university students is a critical issue in higher education, particularly in demanding fields such as medicine. Medical students face high cognitive and emotional demands, making them vulnerable to academic failure. In response to this challenge, the Universidad Francisco de Vitoria (UFV) implemented the Comprehensive Academic Support and Mentoring Program (CASMP) to improve student outcomes.ObjectiveThis study aimed to evaluate the impact of CASMP on the academic performance of medical students at UFV. Specifically, it assessed whether structured academic support contributed to reducing the rate of insufficient academic performance (IAP) and increasing recovery among students at risk of dismissal.MethodsA retrospective observational design was used to analyze academic records from 7,861 students enrolled between the 2010–2011 and 2023–2024 academic years. Students were classified as IAP if they failed to meet the minimum credit requirements defined by institutional regulations. The analysis compared academic outcomes between two periods: pre-CASMP (2010–2011 to 2014–2015) and post-CASMP (2015–2016 to 2023–2024), using chi-square and Mann-Whitney U tests.ResultsThe results showed a significant reduction in the IAP rate following the implementation of CASMP, dropping from 12% to 7%. The percentage of students meeting academic progression standards increased from 88% to 93%. Among students at risk of dismissal, 54% recovered in the following year, with recovery rates exceeding 70% in some cohorts. Although no statistically significant difference was found in dismissal rates, a downward trend was observed over time.ConclusionIn conclusion, the CASMP program has proven effective in improving academic performance and retention among medical students. Structured academic support, including tutoring, mentoring, and preventive interventions, plays a vital role in helping students overcome academic challenges and avoid failure. These findings support the integration of comprehensive support programs in medical education to foster student success.